The Quest for Selfhood in Jaishree Misra’s Ancient Promises - NIMILA S F,; J GIFTLIN IYADURAI, (International Journal of Psychosocial Rehabilitation, 2020)
Jaishree Misra‟s Ancient Promises reflects the mental psyche of Indian women in modern times. The analysis draws a picture of the woman trying to find a space for herself in a highly discriminative world. Misra clearly portraits domestic violence in this novel. Janaki of Ancient Promises represents a new woman who rebels against the patriarchal society by breaking the old traditions and beliefs. Here, Janu suffers a lot to attain her female self. The paper asserts that every woman has an inner self to be exposed.